Influence of Quality Control and Certifications on Performance of Manufacturing Firms in Kenya - Benedict Mutinda Kimwaki (Britain International for Academic Research (BIAR) Publisher, 2023)
Quality control is the process of ensuring that the products, services and processes of a company are of an appropriate quality that meets the set standards and subsequently the needs and expectations of the customers. To ensure the companies have a standard framework of quality control, there are quality standardizing organizations such as ISO which carry out certifications to ensure companies conform with key set standards. Embracing quality control and certification has been found to be an essential move for companies to remain competitive and enhance performance. This however needs a backing from the Kenyan perspective particularly among the manufacturing firms, hence the motivation of this study. Using a descriptive approach, 160 respondents were surveyed through a structured questionnaire. The findings revealed that quality control and certification was essential in enhancing firm performance by enabling the companies to meet the quality standards and assure this to customers. The study concluded that failure by most of the companies to embrace quality certification affected their image and this significantly led to decline in their competitiveness and performance. The study recommended the need for management of manufacturing firms to embrace quality control and certification as a way of enhancing their performance through increased quality assurance to their customers.